Legal Analysis of Bank Accounts With Children's Names As Customers - Silvester Magnus Loogman Palit; William Hendrik Reba; Tumian Lian Daya Purba (Dinasti Research, 2024)
This research, entitled Legal Analysis of Bank Accounts with Children's Names as Customers , was carried out at several Jayapura City Bank branches. The methods used in this research are normative juridical and empirical juridical . The problem of this research is how children as customers can be said to be competent according to the legal rules of agreements related to opening bank savings accounts; Then, is it worth continuing to open an account with a child as a customer as an offer that is in accordance with the subjective requirements of the depositor? So this needs to be researched because there are still banking products that offer savings to child customers . It is hoped that this research can provide input to banks regarding their savings product offerings and knowledge for the people of Jayapura City . There is no uniformity in Indonesian law, the age limit for adult children is determined by the child's actions. One way to protect parties (child customers) who are not yet able to realize their actions and the extent of the legal consequences of their actions is to limit their ability to act.